2020
DOI: 10.1186/s13024-020-00393-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neural network abnormalities in human APP transgenic mice resemble those of App knock-in mice and are modulated by familial Alzheimer’s disease mutations but not by inhibition of BACE1

Abstract: Background Alzheimer’s disease (AD) is the most frequent and costly neurodegenerative disorder. Although diverse lines of evidence suggest that the amyloid precursor protein (APP) is involved in its causation, the precise mechanisms remain unknown and no treatments are available to prevent or halt the disease. A favorite hypothesis has been that APP contributes to AD pathogenesis through the cerebral accumulation of the amyloid-β peptide (Aβ), which is derived from APP through sequential proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 162 publications
(237 reference statements)
6
82
0
Order By: Relevance
“…In this study, these early network defects occurred in C99-accumulating regions and were fully rescued by β-secretase inhibition ( 130 ). In contrast, another recent study reported an absence of rescue of network alterations by β-secretase inhibition in the J20 model, although the levels of both C99 and Aβ were clearly reduced ( 133 ). These data show that synaptic function is governed by complex mechanisms that may be difficult to rescue.…”
Section: C99 Is Toxic and γ-Secretase Inhibitors Potentiate Pathogenimentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, these early network defects occurred in C99-accumulating regions and were fully rescued by β-secretase inhibition ( 130 ). In contrast, another recent study reported an absence of rescue of network alterations by β-secretase inhibition in the J20 model, although the levels of both C99 and Aβ were clearly reduced ( 133 ). These data show that synaptic function is governed by complex mechanisms that may be difficult to rescue.…”
Section: C99 Is Toxic and γ-Secretase Inhibitors Potentiate Pathogenimentioning
confidence: 85%
“…Of importance, C99 accumulation was found to also occur in many other transgenic models including Tg-CRND8 ( 129 ) and JA20 ( 130 ) mice carrying the APPswe mutation, known to increase C99 production, but also in mice displaying the APP E693Q Dutch mutation ( 131 ), in which a C99 overproduction is not expected to occur. Interestingly, and importantly, C99 accumulation also occurs in the knock-in models APP-NL and APP-NL-F, harboring the Swedish (KM670/671NL) mutation alone (APP-NL) or in combination with the I706F mutation (APP-NL-F), respectively ( 132 , 133 ) ( Table 2 ) indicating that C99 accumulation was not just an artificial phenotype linked to APP overexpression, as earlier described for other events taking place in transgenic mouse models that sometimes express very high levels of APP ( 132 ). The presence of the Swedish mutation could indeed, at least to some extent, explain the C99 accumulation in these knock-in mice.…”
Section: C99 Is Toxic and γ-Secretase Inhibitors Potentiate Pathogenimentioning
confidence: 99%
“…(C) Male and female nTG mice take turns earning more pellets initially but by the last stage of the experiment male and female nTG mice earn the same amount. (D) Male APP mice earn more pellets than female APP mice during the second epoch of the last stage (days 23-52) with female APP mice earning more than male APP mice during the last epoch (days [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. (E) Male APP mice earn more pellets than male nTG during the first two epochs in the last stage (days 18-22 and days…”
Section: Resultsmentioning
confidence: 99%
“…Because network activities supporting cognition are altered prior to disease onset in AD and because interneuron dysfunction has emerged as a potential mechanism underlying these network abnormalities (see for review 65 ), we measured the ectopic expression of neuropeptide Y (NPY), a well-established marker of molecular alterations linked to the network remodeling in APP mice 27,32,[66][67][68] , in all mice subjected to RRow. Adapting the approach developed by the Mucke group 66 for confocal imaging analysis, we observed a ~2-fold increase in NPY immunoreactivity in mossy fiber axons in the stratum lucidum (SL) of APP mice (t test, F(1,15) = 3.5321, p = 0.0414; Suppl.…”
Section: Striatal Inhibitory Network Alterations In Male App Micementioning
confidence: 99%
“…By revealing the in vivo effects and underlying mechanisms of suspected causal drivers of AD, they have complemented, expanded, and challenged conclusions drawn from clinical studies. For example, mouse models have shown that human amyloid precursor proteins (hAPP), apolipoprotein E4, and tau can each cause neural network and cognitive dysfunctions independent of the formation of amyloid plaques and neurofibrillary tangles (Raber et al, 1998;Holcomb et al, 1999;Hsia et al, 1999;Mucke et al, 2000;Palop et al, 2003;Van Dam et al, 2003;Cleary et al, 2005;Cheng et al, 2007;Roberson et al, 2007;Wilcox et al, 2011;Huang and Mucke, 2012;Fowler et al, 2014;Maeda et al, 2016;Najm et al, 2019;Zott et al, 2019;Johnson et al, 2020;Chang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%